Klasifikasi Semantik Adjektiva Bahasa Jawa Dialek Malang - Shitadewi, Ida Ayu; Dhanawaty, Ni Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 28 No 1 (2021): MaretDO - 10.24843/ling.2021.v28.i01.p03, 2021)
This research aims at classifying semantic meaning of adjective in Javanese language Malang dialect (to be called BJDM). This research utilizing data taken from daily conversation of BJDM native speakers, as well as from interviewing the native speakers to talk about selected topics such as Malang city now and then, neighborhood, description of family and relatives, description of pets, and neighborhood activities.   Dixon’s (2010) semantic types associated with adjective which classified for universal language is implemented to analyze the data. To provide the data, the researcher interviewed and recorded the native speakers of BJDM. Analysis method used in this research is distributable method with technique of distributing into components.  This research resulted in eight semantic classes of adjective, which are composed of (1) color, (2) age, (3) dimension, (4) speed, (5) value, (6) condition, (7) position, (8) quantity. Some of these classes are specified into subclasses, as in class of color specified into primary color, color pattern, and secondary color, in class of age specified into age for being and thing, in class of dimension specified into shape and measurement, in class of value specified into value related to human, and value related to non-human, and in class of speed specified into time and movement.